Value Added Products from Dikiri Coconuts: Preparation, Compositional and Sensory Qualities - Gunathilake, K. D. P. P.; Jaavidh, M. A. Mohammad; Perera, G. R. P. K.; Thilakahewa, Chamila; Kumara, A. A. N. (International Coconut Community Journal, 2010)
A study was conducted to evaluate Sri Lanka’s dikiri coconut for toffees, Dikiri spread and ice cream. The prepared products were tested for their physico-chemical and sensory properties. Initial trials were done in Sri Lanka to identify the best Dikiri kernel/sugar ratio for toffees, showing that a 1:1 ratio gave acceptable quality. Prepared Dikiri spread was compared with margarine-based bread spread. Results revealed that the product was more acceptable in terms of taste and overall acceptability compared with the margarine-spread. The Dikiri spread comprised 7.95% minerals, 11.35% crude fat, 2.68% crude protein, 4.95% crude fiber and 73.07% carbohydrate on dry weight basis. Dikiri-added ice cream was acceptable and comparable with regular dairy ice cream. Composition of the Dikiri-added ice cream conforms to Sri Lanka Standards.